PENGARUH PROGRAM BAURAN PROMOSI TERHADAP PROSES KEPUTUSAN PEMBELIAN PADA RESTORAN CEPAT SAJI CHICKEN STORY CABANG PONDOK INDAH MALL JAKARTA : Survey Pada Tamu Chicken Story Cabang Pondok Indah Mall Jakarta - Andri Setiadi Nugraha, - (2010)
Market restauran fast food industry in Indonesia is very potential. The development of urban communities and their high mobility becomes an indication oh the ever increasing need for people to eat fast service.Lifestyle changes will also support the demand of fast food, practical and high quality. One fast food Restaurant in Indonesia is the Chicken story by building a business in the segments that are still empty, which is grilled chicken and was ready to face competition from another restauran fast food that has theres in indonesia are likely to offer crispy chicken in their menu. The problem faced by Chiken story Pondok Indah Mall branch that has esperienced decline in sales in recents years, this is supported by sales decline and causing a drop in sales revenues annually ranked among the branches of another Chicken story, who was in Jakarta. The purpose of this research is to know about descriptive of promotion mix, descriptive purchasing decision process, and the influence of promotion mix program on the purchasing decision process at fast food Restaurant industry Chicken Story Pondok Indah Mall Branch Jakarta. Independent Variable (X) in this research is promotion mix programs having dimension advertising (X1), sales promotion (X2), public relation (X3), and direct marketing (X4) and the dependent variable purchasing decision process (Y). The research used explanatory survey method.. It is done less than one year, using cross sectional method. The data used consists of primary data and secondary data, and its data analysis used path analysis. The population of this study was the guest who have purchase transactions with a sample of Chicken Story 110 people. The result shows that the is promotion mix program of Chicken Story is include in medium category. The same thing also hapened in purchasing decision process stay at medium category. From result of counting of path analysis is known is existances of influence purchasing decision process is equal 52.4 %. Therefore, it is recommended that PT Prime Restaurant Indonesia, should increase the frequency promotion mix program as one of its marketing strategy, in order to increase its performance in the market and ensure that it can increase a purchasing decision process